The impact of fibromyalgia on the quality of life of adults (Revista Científica Integrada, 2024)
Introduction: Fibromyalgia is a chronic inflammatory disease, part of the group of rheumatic diseases, where the main symptom is the presence of chronic musculoskeletal pain in various parts of the body. Objective: the objective of the present study is to evaluate the impact that fibromyalgia can have on the quality of life of adults who have this disease. Method: this is a systematic review carried out by searching for articles in the SciELO, Pubmed and Bireme databases, whose search period covered the years 2017 to 2022, in Portuguese, English and Spanish. In total, 615 articles were made available. After the first evaluation, selecting only transversal articles related to the pre-established specific objectives, 21 articles were pre-selected and sent to two reviewers who jointly eliminated 6 articles. Thus, 15 studies were selected and used in this review. Results: among the main results, it was confirmed that fibromyalgia affects the quality of life of affected patients, presenting repercussions in several areas, among which it is worth highlighting the functional, social and psychological aspects, where the main findings were: decreased muscle strength, social withdrawal and increased depression. Conclusion: it is concluded that fibromyalgia negatively impacts the quality of life of affected patients, being a disease with great limiting potential.
Keywords: Fibromyalgia; Quality of life; Chronic pain